2015
DOI: 10.1177/0894439315578240
|View full text |Cite
|
Sign up to set email alerts
|

Advertising for Cognitive Interviews

Abstract: Researchers commonly rely on relatively small convenience samples for cognitive pretesting questionnaires. Methods used to recruit these samples vary depending on the population of interest, study timeline, study budget, and other factors. Over the past decade, one method that has become popular because of these considerations is online classified advertisements (e.g., Craigslist ads). A concern with the use of this recruitment method is that it leads to a set of participants who repeatedly participate in cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The article by Head et al [35] has 2 studies and has been counted as 2 articles for the purpose of Figure 1. In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The article by Head et al [35] has 2 studies and has been counted as 2 articles for the purpose of Figure 1. In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different.…”
Section: Resultsmentioning
confidence: 99%
“…In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different. Out of 30 studies, 12 studies (40%) reported higher rates of recruitment through social media as compared with any of the other methods used [14-17,26,28,31,32,35, 36,41,42] and 15 studies (50%) reported recruitment via social media to be less effective than at least one other method used [18-21,23-25, 27,33-35,37-40]. Heffner et al [20] and Rabin et al [24] found social media to be the least effective method out of multiple (>2) recruitment methods used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More precisely, we used Facebook advertisements to test whether these could be applied to sample migrants and convert them into survey participants. To our knowledge, this method has so far only been applied by a limited number of studies that were all conducted in the area of medical and health research (Arcia, 2014;Chu & Snider, 2013;Fenner et al, 2012;Kapp, Peters, & Oliver, 2013;Lohse, 2013;Ramo & Prochaska, 2012) or to recruit participants for cognitive pretests for which monetary incentives were offered (Head, Dean, Flanigan, Swicegood, & Keating, 2016).…”
Section: Snss As a Sampling Framementioning
confidence: 99%